Internet and its role in Singapore's changing political landscape. - Tan, Chi Ping. (2013)
In the age of the Internet, many have wondered about its effect on social life and on politics as well, especially with the creation of Social Networking Sites (SNS) such as Facebook and Twitter. Singapore has been a country with a one-party rule since its Independence and its citizens have been described as being politically apathetic. However, with the recent turnaround of events in the 2011 General Election (GE) and the continuing change in political tide, the question of why did the political tide in Singapore turn surfaces. This paper is aimed at exploring the role of the Internet – focusing on Social Networking Sites (SNS) in particular – in reducing political apathy in Singapore and in aiding the turn in tide in Singapore’s political scene as well as its potential in being used as a platform for politics in the future.